Resin molding by using electro-activated deposition for efficient manufacturing of carbon fiber reinforced plastic. (15th December 2017) - Katagiri, Kazuaki; Sasaki, Katsuhiko; Honda, Shinya; Nakashima, Hikaru; Tomizawa, Yusuke; Yamaguchi, Shimpei; Ozaki, Tomoatsu; Sonomura, Hirosuke; Kakitsuji, Atsushi
Abstract: A more efficient manufacturing process for CFRP is expected to save energy, time and cost for production. However, it is difficult to impregnate the resin efficiently and uniformly between the carbon fibers, micro void tend to remains and strength decreases. In this study, a novel manufacturing method of CFRP by using the electro-activated deposition resin molding was developed. The non-crimp carbon fiber fabric was immersed in the electro-activated deposition solution, that containing epoxy groups. And, the fabric was energized and heat cured. The electro-activated deposition conditions and tensile properties were investigated for the CFRPs. It was confirmed that resin could be impregnated for multiple plies of the non-crimp carbon fiber fabric without using autoclave and injecting viscous resin like VARTM. Comparing to the traditional manufacturing process, a step of previously mixing an epoxy resin prepolymer and a curing agent was not required. And, a process of vacuum suction could be eliminated, so, wrapping non-crimp carbon fiber fabric with vacuum bag was not necessary.